Komparasi Prinsip Toleransi Beragama dalam al-Qur'an dan Tripitaka - Mizan Alfath (Al Hikmah, 2025)
Tolerance of differences is the primary basis for maintaining state stability. In a country whose citizens adhere to different religions, the holy book can be a link between religions because the holy book contains principles of community life. The holy or sacred book teaches commendable behaviour in society, including tolerance. By exploring the concept of tolerance in the Quran and Tripitaka, it is hoped that it can communicate Islam and Buddhism in inter-religious tolerance. This study uses the literature analysis method to identify and analyze several sources related to religious tolerance in the Quran and Tripiaka. The main findings of this study indicate that religious tolerance in the Quran emphasizes doing good and being fair even though people are of different religions, not forcing people to become Muslims, not insulting the gods of other faiths, and adhering to their respective religions. Topics related to tolerance in the Tripiaka include not being fanatical about religion, not being forced to become Buddhist, and responding to insults with kindness. Both holy books express equal rights for living beings regardless of religion.